Characteristic of Oyster Mushroom Grown on Substrates Containing Paper Waste - Joko Sulistyo; Soh Chin Quan; Lee Khaa Hwee (Jurusan Biologi Universitas Negeri Makassar, 2023)
The aim of study was to determine the capacity of spawn of oyster mushroom and influence of substrates containing PW used to grow the mushroom and its properties related to nutritional value and antioxidant activity due to the use of paper waste (PW). The substrate was prepared based on 5 different formulations which were 0% (control), 20%, 30%, 40%, 50% PW. Preparation of seeds and spawn and mushroom cultivation technique was carried out manually using basic techniques of mushroom seeding and cultivation, while proximate analysis was carried out to analyze the content of fat, protein, moisture, and ash of the mushroom fruiting bodies, followed by analysis of heavy metals using AAS, and furthermore carried out extraction of bioactive compounds to analyze antioxidant activity using ABTS oxidizer. The physicochemical analysis was carried out to test the quality of the mushroom. Overall, the mushroom grown on the substrates containing 50% PW showed higher content of ash, protein, fat and crude fiber compared to the mushroom grown on other substrates with different composition of PW. However, the mushroom grown on the substrate contained 50% PW indicated considerably high content of heavy metals such as lead, (3.5%), copper (20.8%) and cadmium (4.4%), respectively, although, it showed the higher antioxidant activity (87.19%) as well compared to the mushrooms grown on the substrate containing a lower percentage of PW, thus giving a conclusion that there was probably positive correlation in between the heavy metals contained in PW with antioxidant activity.